FAKTOR - FAKTOR INTERNAL DAN EKSTERNAL TERHADAP KEPATUHAN PASIEN TB PARU DI PUSKESMAS PADANG BULAN TAHUN 2019 - ANGELA TRISNAWATI PADANG; DONAL NABABAN; NETTI ETALIA BR. BRAHMANA (LP2MTBM MAKARIOZ, 2022)
Tuberculosis (TB) is a disease caused by the bacterium Mycobacterium tuberculosis and includes zonosis disease becauseit can be transmitted by animals to humans. TB is transmitted by germs in very small water points that can be inhaled whenpeople with active TB cough, sneeze, laugh or talk. Padang Bulan Health Center is located in Medan Baru District with aworking area of six villages. Based on the results of a preliminary survey conducted by researchers, outpatients who visitedPadang Bulan Health Center during 2017 amounted to 128 people and in 2018 amounted to 161 people. This numberincludes new patients, relapsed patients, and Multi Drug Resistant (MDR) patients. This study is an analytical study with across sectional approach to find out internal factors and external factors for the recovery of lung TB sufferers in PadangBulan Health Center. The population in this study was all people with pulmonary TB who underwent treatment at PadangBulan Health Center in 2019, which was 185 people and a sample of 69 people. The results showed that there was arelationship between age (0.024), knowledge (0.012), PMO role (0.021), health worker role (0.031), family support (.030),drug side effects (0.032) and duration of treatment (0.024). The most dominant variable associated with the compliance oftuberculosis sufferers is knowledge that is (p = 0.001; OR= 0.007). It is recommended for the Puskesmas to be more leveledin supervising and paying more attention to tuberculosis patients.